Microbial Fuel Cells for Simultaneous Electricity Generation and Organic Degradation from Slaughterhouse Wastewater - Christwardana, Marcelinus; Prabowo, Adrianus Kristyo; Tiarasukma, Agnes Priska; Ariyanti, Dessy (International Journal of Renewable Energy Development, 2016)
Microbial fuel Cell (MFC) has gained a lot of attention in recent years due to its capability in simultaneously reducing organic component and generating electricity. Here multicultural rumen microbes (RM) were used to reduce organic component of slaughterhouse wastewater in a self-fabricated MFC. The objectives of this study were to determine the MFC configuration and to find out its maximum capability in organic degradation and electricity generation. The experiments were conducted by employing, different types of electrode materials, electrode size, and substrate-RM ratio. Configuration of MFC with graphite-copper electrode 31.4 cm2 in size, and substrate-RM ratio 1:10 shows the best result with current density of 318 mA m-2, potentialÂ  2.4 V, and achieve maximum power density up to 700 mW m-2. In addition, self-fabricated MFC also shows its ability in reducing organic component by measuring the chemical oxygen demand (COD) up to 67.9% followed by increasing pH from 5.9 to 7.5. MFC operating at ambient condition (29oC and pH 7.5), is emphasized as green-technology for slaughterhouse wastewater treatment.Â Article History: Received March 26, 2016; Received in revised form June 20, 2016; Accepted June 25, 2016; Available onlineHow to Cite This Article: Prabowo, A.K., Tiarasukma, A.P., Christwardana, M. and Ariyanti, D. (2016) Microbial Fuel Cells for Simultaneous Electricity Generation and Organic Degradation from Slaughterhouse Wastewater. Int. Journal of Renewable Energy Development, 5(2), 107-112.http://dx.doi.org/10.14710/ijred.5.2.107-112Â